Molecular and Biochemical Changes of Some Algae Used in the Biological Removal of Heavy Metals in Industrial Waste Water Treatments - Kareem Talib Kahashan (Journal of Global Pharma Technology, 2018)
The current study examined the susceptibility of three types of algae, including Oscillatoria sp., Westiellopsis prolifica, Stigonemasp in reducing the values of some heavy metals in industrial wastewater. These algae were used as unialgal culture and the wastewater was used from the industrial wastewater disposed by the State Company for Textile Industries as a growth culture for the development of these algae by cultivating each algae alone in wastewater under constant laboratory conditions at 25 ± 20 ° C and in a light system 16: 8 hours Illumination: Darkness.  The results showed that the Oscillatoria sp has the ability to reduce heavy metals in high ratios reduction of (100.3%) for Iron and (29.1%) for Copper and (66.2%) for Zinc and (33.5%) for Cadmium and (99.5%) for Lead. The results also indicated that W. prolifica showed the ability to reduce heavy metals by (99.7%) for Iron and (29.1%) for Copper and (56.4%) for Zinc and (40.2%) for Cadmium and (99.5%) for lead. Stigonemasp showed higher efficiency than the rest of algae in reduction of some heavy metals with ratio of (100%) for Iron and (44.3%) for Copper and (73.8%) for Zinc and (22.3%) for Cadmium and (100%) for lead .As for the current algae physiological status, Glutathione (GSH) content in  Oscillatoria sp was decreased after treatment, while its content was increased in W. prolifica, Stigonema sp. after treatment. The content of the Cytochrome p450 in the algae appears to have decreased after treatment in Oscillatoria sp. And W. Prolific and increased in Stigonema sp. The results indicate that the Metalothionine content has not increased significantly and the values remain similar to the algae shown for control. On the other hand, bioremediation showed a clear effect on molecular properties of algae, this was demonstrated by the high values of Comet assay indicators, which include tail length, Comet length, tail moment which indicate the effect of treatment on DNA after completion of the treatment.